Potensi Pelanggaran Lalu Lintas Di Simpang Mayang Tujuan Jambi Town Square Mall - Ade Nurdin (Universitas Batanghari, 2020)
One of the biggest factors causing traffic accidents is a violation committed by drivers who are less orderly in traffic. This research was conducted on Jalan Kapten A. Bakarudin Simpang Mayang, Jambi Town Square Mall (Jamtos mall). The research objective is to find out how much the traffic sign violations at the Intersection of Jamtos mall. The results show that the highest traffic sign violations occurred on Sunday, August 16, 2020, with 1996 vehicles : 1494 two-wheeled vehicles and 502 four-wheeled vehicles. Meanwhile, the vehicles that enter Jamtos mall consist of 519 two-wheeled vehicles and 237 four-wheeled vehicles with the highest violation rate of two-wheeled vehicles at 19.00-20.00 WIB totaling 145 vehicles and 52 four-wheeled vehicles at 13.00-14. 00 WIB. The largest percentage of traffic violations to the Jamtos mall destination occurred on Tuesday, August 18, 2020, amounting to 41%, hereby stating that there was a large turn-around traffic sign violation.